2021
DOI: 10.3389/fonc.2021.779748
|View full text |Cite|
|
Sign up to set email alerts
|

Ribosomal Protein L23 Drives the Metastasis of Hepatocellular Carcinoma via Upregulating MMP9

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths globally. Tumor metastasis is one of the major causes of high mortality of HCC. Identifying underlying key factors contributing to invasion and metastasis is critical to understand the molecular mechanisms of HCC metastasis. Here, we identified RNA binding protein L23 (RPL23) as a tumor metastasis driver in HCC. RPL23 was significantly upregulated in HCC tissues compared to adjacent normal tissues, and closely related to poor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…14 RPL23 is a gene that encodes ribosomal protein L23 and its high gene expression level relates to unfavourable events in diverse cancer diseases. [16][17][18] Herein, we demonstrated that the RPL23 gene expression level was elevated in AMI exosome samples. Furthermore, our analysis indicated that RPL23 was positively correlated with the fractions of monocyte-derived exosomes and negatively correlated with the fractions of resting mast cell-derived exosomes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…14 RPL23 is a gene that encodes ribosomal protein L23 and its high gene expression level relates to unfavourable events in diverse cancer diseases. [16][17][18] Herein, we demonstrated that the RPL23 gene expression level was elevated in AMI exosome samples. Furthermore, our analysis indicated that RPL23 was positively correlated with the fractions of monocyte-derived exosomes and negatively correlated with the fractions of resting mast cell-derived exosomes.…”
Section: Discussionmentioning
confidence: 74%
“…RPL23 is a gene that encodes ribosomal protein L23 and its high gene expression level relates to unfavourable events in diverse cancer diseases 16–18 . Herein, we demonstrated that the RPL23 gene expression level was elevated in AMI exosome samples.…”
Section: Discussionmentioning
confidence: 76%
“…Increasing evidence shows that there are about 80 kinds of ribosomal proteins in eukaryotes, which not only function to form ribosomes and bind RNA but also have other functions, such as participating in tumor development and regulating tumor resistance to drugs 11,21 . Today, many ribosomal proteins have been found to be involved in regulating the occurrence and development of a variety of cancers, including lung, breast, and liver cancers 11,12,22 . In addition, RNA‐binding protein (RBP), a key regulator of gene expression, is involved in the progression of many cancers, such as HCC 22–24 .…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 21 Today, many ribosomal proteins have been found to be involved in regulating the occurrence and development of a variety of cancers, including lung, breast, and liver cancers. 11 , 12 , 22 In addition, RNA‐binding protein (RBP), a key regulator of gene expression, is involved in the progression of many cancers, such as HCC. 22 , 23 , 24 A total of 526 RBPs were abnormally expressed in HCC compared to normal adjacent liver tissues and predicted poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation